Evaluasi Ekonomi dan Transparansi Kontrak Gross Split dan Cost Recovery dalam Pengelolaan Hulu Migas di Indonesia - Rafid Endika; Edy Soesanto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Transparency in the management of upstream oil and gas contracts in Indonesia is crucial to ensure the efficient and accountable management of natural resources. The two main contract schemes applied, Cost Recovery and Gross Split, each face challenges related to transparency. In the Cost Recovery scheme, transparency issues are related to the verification of costs submitted by contractors, while in the Gross Split scheme, transparency is needed in determining objective production-sharing parameters. Digital technology emerges as a solution to improve accountability, but its implementation requires strong regulatory support and infrastructure investment. The principle of good faith between the government and contractors is also a key factor in achieving effective transparency. Strengthening the capacity of SKK Migas as the regulatory body and ensuring information openness to the public are essential to building trust and creating sustainable management.